Analysis of the most productive forms (Camellia sinensis (L.) O. Kuntze) in the collection-breeding plot during the research period - S. V. Loshkareva (Новые технологии)
The article considers the productivity of the most promising forms of tea in the collection-breeding plot in the village of Uch-Dere, Sochi. The data on the productivity of the selected forms for two years of the research, both by year and in the context of yield dynamics during the collections for the growing season in 2017 have been presented. More productive stable forms have been defined (13-09, 13-13, 13-23). There has been a difference in yield in all forms, including control 79-79, depending on weather conditions of the current and previous research period from 8.7% (form 13-23) to 37.3% (form 13-25), with an average indicator of 23.7%. A correlation analysis of all forms has been carried out and a direct close connection has been revealed between indicators such as the height and width of the trellis (the correlation coefficient between them is 0.84) and between productivity and the length of the flush (0.74).